PHYSICAL DEVELOPMENT OF GIRLS PARTICIPATING IN BASKETBALL TRAINING ACTIVITIES - P. Mavrudiev; I. Hristov (Trakia Journal of Sciences)
The aim of the present study is to establish the impact of basketball classes on the physical development of 14-year-old girls from the basketball club "Toni - 7" - Sliven. The subject of research is the physical development and physical capacity of students who participate systematically in basketball training sessions. The object of study is the signs of physical development of 14-year-old girls. A total of 19 girls participated in regular basketball training sessions. For the needs of the research, anthropometric measurements were performed and BMI was calculated. To achieve this goal we applied the following mathematical and statistical methods: Variation analysis, comparative and frequency analysis, index method, and Student's t-test.